The Association of Severe Tricuspid Regurgitation with Poor Survival Is Modified by Right Ventricular Pressure and Function: Insights from SHEBAHEART Big Data - Itelman, Edward; Vatury, Ori; Kuperstein, Rafael; Ben-Zekry, Sagit; Hay, Ilan; Fefer, Paul; Barbash, Israel; Klempfner, Robert; Segev, Amit; Feinberg, Micha; Guetta, Victor; Maor, Elad (Journal of the American Society of Echocardiography, 2022)
Contemporary data on the independent association of severe tricuspid regurgitation (TR) with excess mortality are needed. The aims of this study were to describe contemporary outcomes of patients with severe TR and to identify outcome modifiers. Consecutive echocardiographic reports linked to clinical data from the largest medical center in Israel (2007-2019) were reviewed. The primary outcome was all-cause mortality. Cox regression and propensity score matching models were applied. The final cohort included 97,096 patients. Mild, moderate, and severe TR was documented in 27,147 (28%), 2,844 (3%) and 1,805 (2%) patients, respectively. During a median follow-up period of 5 years (interquartile range, 2-8 years), 22,170 patients (23%) died. Kaplan-Meier survival analysis demonstrated an increased risk for death with an increasing degree of TR (log-rank P < .001). Propensity score matching of 1,265 patients with severe TR and matched control subjects showed that compared with those with nonsevere TR, patients with severe TR were 17% more likely to die (95% CI, 1.05-1.29; P = .003). The association of severe TR with survival was dependent on estimated right ventricular (RV) pressure, with a more pronounced effect among patients with estimated systolic pressure ≤ 40 mm Hg (hazard ratio, 2.12 vs 1.04; P for interaction < .001). A landmark subanalysis of 17,967 patients demonstrated that RV function deterioration on follow-up echocardiography modified the association of severe TR with survival. It was more significant among patients with preserved and stable RV function (P for interaction = .035). The outcome of severe TR is modified by RV pressure and function. Once RV function deteriorates, differences in the outcomes of patients with and without severe TR are less pronounced. •Severe TR is independently associated with poor survival.•The outcome of severe TR is modified by RV pressure and function.•Severe TR association with survival is more pronounced at RVSP < 40 mm Hg.•As RV function deteriorates, severe TR association with outcome is less pronounced.•Efforts should focus on patients with normal RVSP and preserved RV function.